The End All Around Us : Apocalyptic Texts and Popular Culture. - Walliss, John (Millennialism and society., 2014)
The Apocalypse or end times are a recurrent theme within contemporary popular culture. 'The End All Around Us' presents a wide-ranging exploration of the influence of the apocalypse within art, literature, music and film. The essays draw on representations of the apocalypse in heavy metal music, science fiction, disaster movies and anime. The book examines key apocalyptic texts, focusing on their relevance to today. It will be invaluable to all those interested in the religious and cultural impact of apocalyptic thought.